Agent-based model for social and sexual partnerships formation. (February 2015) - Mudimu, Edinah; Engelbrecht, Gerhard Nieuwoudt
This paper presents an agent-based model that aims to replicate the social and sexual partnerships in real-world settings. This work is part of work in progress and aims to model the progression of HIV in a community. The model builds on existing models allowing for marriage, divorce and agent death. The main aim of this paper is to enhance the understanding of the evolution of social and sexual partnerships in a dynamically changing agent population. Agents are assigned attributes such as attractiveness, aspiration, courtship duration and sexual drive. Partnership formation is based on a likeability index which is calculated using age, aspiration and attractiveness.